1973
DOI: 10.1152/ajplegacy.1973.225.3.675
|View full text |Cite
|
Sign up to set email alerts
|

Central and peripheral circulatory changes after training of the arms or legs

Abstract: increase in stroke volume or other central circulatory JENS TRAP-JENSEN. Central and peripheral circulatory changes after training of the arms or legs. Am.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

15
109
0
4

Year Published

1981
1981
2012
2012

Publication Types

Select...
4
3

Relationship

0
7

Authors

Journals

citations
Cited by 225 publications
(128 citation statements)
references
References 0 publications
15
109
0
4
Order By: Relevance
“…This hemodynamic response cannot be explained by changes in LV filling alone, since EDVr and ESVr both decline at this point. We could not measure arterial blood pressure during arm cranking in this study, but previous studies have shown higher SBPs during arm exercise at comparable HRs (7,8,12). It remains possible that postexertional reduction in afterload or increased LV contractility contributed to this response.…”
Section: Arms Vs Leg Exercise: Comparison Of LV Responsementioning
confidence: 86%
See 2 more Smart Citations
“…This hemodynamic response cannot be explained by changes in LV filling alone, since EDVr and ESVr both decline at this point. We could not measure arterial blood pressure during arm cranking in this study, but previous studies have shown higher SBPs during arm exercise at comparable HRs (7,8,12). It remains possible that postexertional reduction in afterload or increased LV contractility contributed to this response.…”
Section: Arms Vs Leg Exercise: Comparison Of LV Responsementioning
confidence: 86%
“…The Frank-Starling mechanism is a key determinant of LV function during leg exercise (5,18,20,27,43,48) and orthostatic challenges alone can limit ventricular filling pressures and reduce SV (4). Despite recruitment of neurohumoral mechanisms to augment hemodynamics during arm exercise (i.e., peripheral vasoconstriction and augmented arterial pressure), LV filling remained less than leg exercise (2,7,8,28). The attenuated LVEF response during arm exercise may also be related to limited systolic function.…”
Section: Arms Vs Leg Exercise: Comparison Of LV Responsementioning
confidence: 98%
See 1 more Smart Citation
“…O componente isométrico do trabalho de estabilização do corpo, realizado pela musculatura dos MMSS e do tórax, provoca elevação acentuada da pressão arterial (PA) [3][4][5][6][7][8] . A freqüência cardíaca (FC) encontra-se elevada no iní-cio dos programas de treinamento, especialmente nos portadores de lesão medular alta (>T6), nos quais há alteração do centro de controle cardiovascular da medula [5][6][7][8][9] .…”
Section: Riscos De Doença Arterial Coronária Em Deficientes Físicos Dunclassified
“…Alterações em parâmetros circulatórios centrais e periféricos foram comparados por Clausen e col 4 , utilizando metodologia invasiva antes e após treinamento de alta e moderada intensidade de MMSS e MMII, respectivamente. Foram observados aumento do VO2máx (9,9 a 15,9%), e do trabalho total no grupo de treinamento de alta intensidade.…”
Section: Ergometria De Membros Superiores -unclassified